(3OjhGf GHf RjOhfs - (3GHf RjOhf , CHh GdhdjO CMeO Hf YHO Gddg Hf ZGdH Hf RjOhf GdeNRhej GdCfOdSj, CHh GdhdjO,J (B463 (3g` s ((3eMeO YHOGddg GdReQGfj s)
(3ChdgG (B:s
(3bGd GdhRjQ CHhGdhdjO CMeO jeOM CHG GdMRe Hf LghQ CMO edhc GdWhGFa gPG GdUHGM Ydi SQGc QbjHG aUdi HaQYc djdc GdZQHjHG s
(3BNQgG (B:s
(3hEfj deG Jhpdi hChdrjJ TGcQ aef TcQ GdfYeGA fGd QVi GdQH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B158 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B284s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B485 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B112 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B(443 (3YehejI (B7039) s
Keywords: (3GdCOHs